Lectura crítica en el proceso de enseñanza – aprendizaje del área de lengua y literatura de los estudiantes del quinto año de Educación General Básica de la Escuela Fiscal Mixta “24 de Mayo de la parroquia San Juan, cantón Puebloviejo, provincia de “Los Ríos” período lectivo 2012 - Candel Gutiérrez, Rosa Lidia (2012)
Critical reading is called the approach to a text which seeks to obtain a more analytical content of the text, concerns the interpretation and critical understanding of the text, is it the reader is not a passive, but active in the reading process, ie decodes the message, questions, analyze it, critique it, and so on. The lack of techniques to improve reading comprehension in students causes low participation, since they need to be motivated. The carelessness of the teacher to correct the problems of reading makes students feel a negativity to work and exercise in understanding, leading to conformity and mediocrity in every one of them. Thus is lost more likely to acquire information as to integrate reading and meaningful learning involves a close relationship and to teach students to read and understand and read mechanically contributes to enhance their learning substantially, making them more aware and sensitive to the educational reality. Our research, explores the importance of using these teaching strategies in developing critical reading, describing why it is essential to consider the appropriate application of educational strategies. From this point of view our project is about: CRITICAL READING ON THE PROCESS OF TEACHING - LEARNING AREA OF LANGUAGE AND LITERATURE OF THE FIFTH YEAR STUDENTS GENERAL EDUCATION BASIC SCHOOL JOINT TAX "ON MAY 24, THE JOHN PARISH, Puebloviejo CANTON, PROVINCE OF RIVERS IN THE SCHOOL YEAR 2012 The above issue is intended to establish basic guidelines for teachers on the use of critical reading in the teaching - learning in an efficient manner. Thus, their main goal is to provide critical reading strategies to improve the development of the teaching - learning the language arts area, this could be achieved by raising awareness and encouraging teachers to implement in their daily procedures that are related to the issues raised by the student through their educational process and which to be keeping the Update and Enhancement of basic general education. This research consists of four chapters structured as follows: Chapter I refers to a theoretical framework which is divided into, Scientific Theory, Legal Framework, Theory and Theory Conceptual Reference. In scientific theory is a theoretical framework through important scientific content related to variables, providing them the necessary support to research work and also be very useful to enrich the knowledge of the different actors involved in the project. In the legal framework, consisting articles on the rights of education, drawn from the Constitution of Ecuador, thus fully abalizando research work. The conceptual theory is a conceptual composition of a number of important terms that need a well-defined scientific clarification. To conclude with the theoretical framework we have the theory of reference, which referred to the object and place of study, exposing important data from the educational institution in which research has been developed. Chapter II consists of methodological strategies, including the following elements of research; The purpose, level and location of research, techniques and tools for data collection, the universe, and data processing the methods used. Chapter III, called Data Analysis and Interpretation addresses the following aspects: the statistical tables and charts, source information, the interpretation of each of the questions in the survey of teachers and students, hypothesis testing, conclusions and recommendations. All these data were key factors in designing a proposal to give solution to the problem. Chapter IV is composed of a proposal by which we present some teaching strategies to strengthen students' critical reading and will undoubtedly be a great contribution to develop meaningful learning of the language arts area.